U-NeedKC: Development of a knowledge center in the building engineering education environment to support infrastructure transformation in the industry 5.0 era - Helen Libastari; Alfandi Ziqri (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: The rapid development of digital technology and the emergence of the Industry 5.0 era require higher education institutions to transform into systems that are adaptive, collaborative, and technology-driven. However, the academic culture of digital writing and knowledge sharing among students of the Building Engineering Education program remains low. To address this gap, this study develops an initial design of U-NeedKC, a web-based Knowledge Center intended to support collaboration, training, and flexible academic information access. Methods: This research adopts the R&D approach using the 4D model (Define, Design, Develop, Disseminate), with a current focus on the design phase. Data were collected through observations, interviews, and literature reviews involving students and lecturers to identify user needs. Findings: The findings indicate that users face significant challenges related to limited digital literacy, suboptimal use of existing LMS features, technical constraints, and the absence of an integrated knowledge-sharing culture that supports collaboration and academic literacy. Based on these needs, the study produced the conceptual design of U-NeedKC, a web-based Knowledge Center integrating course modules, digital archives, workshops, discussion forums, and a point system, developed using user-centered and knowledge management principles. This design is expected to enhance learning engagement, information accessibility, collaborative practices, and digital competencies, although its effectiveness has not yet been empirically tested. Conclusion: This study concludes that the initial design of U-NeedKC represents a strategic educational innovation to strengthen digital writing culture and knowledge-sharing practices in higher education. By integrating collaborative features such as learning resources, discussion forums, training modules, and incentive-based engagement, the platform has the potential to foster a sustainable academic ecosystem that supports adaptive learning, social interaction, and institutional transformation in response to the demands of Industry 5.0. Novelty/Originality of this article: This study introduces a web-based Knowledge Center that integrates digital technology with collaborative learning practices to strengthen knowledge sharing and support sustainable educational transformation in higher education.